Explaining COVID-19 Vaccine Rejection Using Social Cognitive Theory in Qassim, Saudi Arabia - Aseel Ali AlSaeed; Unaib Rabbani (Vaccines, 2021)
Acceptance of COVID-19 vaccines needs a health promotion approach to address various social, environmental and personal factors leading to vaccine hesitancy. We assessed the vaccine hesitancy rate and applied social cognitive theory (SCT) to understand COVID-19 vaccine rejection in Qassim, Saudi Arabia. A cross-sectional study was conducted among visitors of 10 randomly selected primary health care centers in Buraidah, Saudi Arabia. Data was collected by a self-administrated questionnaire. The variables were grouped into six constructs of SCT. Logistic regression was used to assess the predictors of vaccine rejection. Out of 486 participants included in the study, 30.5% rejected the vaccine. The most common reason for vaccine rejection was uncertainty about the vaccine’s effectiveness (78%). Among various constructs of SCT, reciprocal determinism (nationality, income and suffering from COVID-19 infection), behavioral capability (knowledge about vaccine safety), self-efficacy (registered for vaccine), and observational learning (getting the vaccine after friends and family members) were significant predictors. Expectation and reinforcement constructs did not show significant association. There was high vaccine rejection in Qassim, KSA. This calls for further improving the mass education strategies. Social cognitive theory can be used to predict vaccine rejection and to develop strategies to increase the utilization of COVID-19 vaccines in Saudi Arabia.